Application of reservoir exergy profile analysis by wellbore simulation on Olkaria Domes geothermal field. (November 2022) - Bett, Alvin Kiprono; Jalilinasrabady, Saeid
Highlights: Previous studies have not linked the surface and sub-surface in Olkaria and other geothermal fields worldwide. The wellbore simulator connected the wellhead, and the reservoir simulated pressure and temperature logs for Olkaria Domes in Olkaria, a liquid-dominated geothermal field. The simulation results enabled the calculation of exergy values at any depth using the pressure and temperature between the reservoir and wellhead. Obtained results of the research used to interpret heat transfer between geothermal reservoir layers and the location of the reservoir. The study demonstrates the importance of connecting the reservoir and wellhead via a wellbore simulation and exergy profiles. Abstract: Geothermal is the energy for the future and is eco-friendly. Exergy analysis of geothermal power plants has been referenced based on wellhead and surface environment conditions. Previous studies have not linked the surface and sub-surface in Olkaria and other geothermal fields worldwide. The wellbore simulator connected the wellhead, and the reservoir simulated pressure and temperature logs for Olkaria Domes in Olkaria, a liquid-dominated geothermal field. The simulation results enabled the calculation of exergy values at any depth using the pressure and temperature between the reservoir and wellhead. Obtained results of the research used to interpret heat transfer between geothermal reservoir layers and the location of the reservoir. This study takes the exergy analysis to the source of geothermal brine under saturated conditions. The paper presents exergy profiles of geothermal wells at Olkaria Domes. The field data input parameters were wellhead pressure, mass flow rates of steam and brine, wellbore diameter, and the reservoir depths (deeper/second and shallow). A wellbore model developed in 1988 was used to simulate temperature-pressure profiles. The thermodynamic parameters (temperature and pressure) from the wellbore simulator were input parameters in the Engineers Equation Solver (EES) code to calculate entropy, enthalpy, and specific exergy. The wellbore exergy profiles show estimated feed zone depths of -1000 - (-) 2800 m.a.s.l for two-directional and three vertical wells. The profiles predicted convective and conductive heat transfers points. For wellhead temperatures of between 182 -205°C, the reservoir temperatures from the wellbore simulator are high at 292°C. The formation pressures were between 3, 978 to 7, 710 kPa. Exergy wellbore simulation of the geothermal reservoir predicted the reservoir and heat transfers in the sub-surface. The study demonstrates the importance of connecting the reservoir and wellhead via a wellbore simulation and exergy profiles.